Non-invasive 11C-Imaging Revealed the Spatiotemporal Variability in the Translocation of Photosynthates Into Strawberry Fruits in Response to Increasing Daylight Integrals at Leaf Surface - Miyoshi, Yuta; Hidaka, Kota; Yin, Yong-Gen; Suzui, Nobuo; Kurita, Keisuke; Kawachi, Naoki (Frontiers in Plant Science, 2021)
The efficiency of photosynthate translocation from leaves to fruits directly affects dry matter partitioning. Therefore, controlling photosynthate translocation dynamics is critical for high-yield and high-quality fruits production. Accordingly, photosynthate translocation changes must be characterized using data obtained at a higher spatiotemporal resolution than that provided by conventional methods. In this study, 11C-photosynthates translocation into strawberry (Fragaria × ananassa Duch.) fruits in individual plants was visualized non-invasively and repeatedly using a positron-emission tracer imaging system (PETIS) to assess the spatiotemporal variability in the translocation dynamics in response to increasing daylight integrals (i.e., 0.5 h, 4.5 h, and 9 h exposures to 400 µmol m-2 s-1 at the leaf surface). Serial images of photosynthate translocation into strawberry fruits obtained from the PETIS confirmed that 11C-photosynthates were translocated heterogeneously into each fruit on the same inflorescence. The amount of translocated 11C-photosynthates and the translocation rate into each fruit significantly increased as the integrated light intensity at the leaf surface increased. An analysis of the pedicel of each fruit also confirmed that the photosynthate translocation rate increased. The cumulated photosynthesis in leaves increased almost linearly with during the light period, suggesting that an increase in the amount of photosynthates in leaves promotes the translocation of photosynthates from leaves, resulting in an increase in the photosynthate translocation rate in pedicels and enhanced photosynthate accumulation in fruits. Additionally, the distribution pattern of photosynthate translocated to fruits did not change during the light period, nor did the order of the sink activity (11C radioactivity / fruit dry weight), which is the driving force for the prioritization of the 11C-partitioning between competing organs, among fruits. Thus, this is the first study to use 11C-radioisotopes to clarify the spatiotemporal variability in photosynthate translocation from source leaves to individual sink fruits in vivo in response to increasing daylight integrals at a high spatiotemporal resolution.